Implementation Of Admission of New Students Zoning System Perspective of Islamic Education Management Theory At SMAN 1 Rambutan - KMS Badaruddin (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to determine the implementation of the admission of new students to the zoning system from the perspective of Islamic education management theory at SMAN 1 Rambutan. The problem discussed is how to implement the zoning system from the Islamic education management theory perspective in the admission of new students at SMAN 1 Rambutan. The type of research used is descriptive qualitative by researching directly into the field. The data collection techniques used were observation, interviews, and documentation. Data analysis techniques in this study are data collection, reduction, presentation, and verification. The results of this study show that the implementation of the admission of new students from the perspective of Islamic education management theory at SMAN 1 Rambutan has gone well, including motivating by rewarding teachers, conducting guidance and guidance direction, establishing good coordination, and communication.